Limnoperna fortunei colonization and macrofouling on net cages in a subtropical reservoir (Brazil) - de Rezende Ayroza, Daercy Maria Monteiro; de Melo, Taissa Juliana [UNESP]; Faria-Pereira, Lilian Paula; Petesse, Maria Letizia; Rebelo, Mauro de Freitas; do Carmo, Clóvis Ferreira; Cataldo, Daniel Hugo (Hindawi, 2021)
We evaluated the spatiotemporal distribution of Limnoperna fortunei larvae, its abundance in relation to other zooplanktonic organisms (copepoda and cladocerans), and its macrofouling on net cages in the Chavantes Reservoir, Brazil. We also estimated its growth rate under this condition and limnological variables in the water column. Zooplankton densities were positively related to water temperature, and copepoda was the most abundant group. L. fortunei showed the highest density in November and March (18.565 to 30.014 larvae/m3) and the lowest from June to August (1.587 to 876 larvae/m3). Population parameters of L. fortunei, as derived from von Bertalanffy seasonal growth function, indicated fast annual growth (K = 1.22) in length in the first, second and third years of life at 21, 28, and 30 mm, respectively. We estimate that 62.920 juveniles/m2 will be recruited annually in fish farming, mainly in the reproductive period, which should be the focus of prevention methods. Our work is the first report to associate the abundance of L. fortunei larvae in the water column with the recruitment of juveniles.
Keywords: fish farm; golden mussel; invasive species; macrofouling; subtropical reservoirs